Dampak Kewirausahaan terhadap Pembangunan Manusia di Negara-Negara Islam - Suranto Suranto; Madha Adi Ivantri (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this paper is to investigate the roles of entrepreneurship on human development in Islamic countries. In order to achieve the study objective, the econometric strategy has been used. The analysis technique is done using Fixed Effect (FE) and Random Effect (RE) estimation from the data panels of the OIC countries in the period 2006-2020. The estimation results show that entrepreneurship and access to finance have positive impact on human development. This study uses samples based on data availability. Therefore, further research is expected to be able to find other proxies from entrepreneurship with more data. In addition, research on entrepreneurship should be classified based on the level of economic development, because there are indicated differences in entrepreneurial characteristics at each level of economic development.